Pengaruh Keunikan, Kualitas, dan Kesesuaian Harga pada Produk Tabungan terhadap Keunggulan Bersaing di Bank Sumut Kantor Cabang Syariah Medan Katamso - Asra, M Rifki; Nasution, Yenni Samri Juliati; Nasution, M. Lathief Ilhamy (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study is entitled "The Influence of Uniqueness, Quality, and Price Conformity in Savings Products on Competitive Advantage at Bank SUMUT KC Syariah Medan". This study aims to find out whether the uniqueness, quality, and price suitability of savings products have a partial or simultaneous effect on competitive advantage at Bank SUMUT KC Syariah Medan Katamso. This research uses the type of associative research. The dependent variable (Y) in this study is competitive advantage, the independent variable is the uniqueness of the savings product (X1), the quality of the savings product (X2), and the price suitability of the savings product (X3). The population in this study were customers of Bank SUMUT KC Syariah Medan with a total sample of 100 respondents using a probability sampling technique. Data collection is done by distributing questionnaires to customers. Data analysis used SPSS Statistics 20.00 with multiple regression. The results of the study revealed that in the T test variable X1 (uniqueness of savings products) had a significant positive effect on competitive advantage, variable X2 (quality of savings products) had a significant positive effect on competitive advantage, and variable X3 (price appropriateness) had a significant positive effect on competitive advantage. Based on the results of the F test, it was found that the uniqueness, quality, and price suitability of savings products have a simultaneous effect on Competitive Advantage. In the Coefficient of Determination Test (R2) it can be seen that the Adjusted R Square value obtained is 0.656 (65.6%). This shows that the independent variables X1 (Unique Savings Products), X2 (Quality of Savings Products), and X3 (Price appropriateness of Savings Products) have a strong ability (0.60-0.799) in explaining variations in the dependent variable Y (Competitive Advantage). . The remaining 34.5% will be influenced by other factors which cannot be explained in this study. Keywords: savings product uniqueness, savings product quality, savings product price appropriateness, competitive advantage.